The Relationship of Depression Levels to Quality of Life in Patients Non-Hemorrhagic Stroke at M.M Dunda Limboto Hospital - Cindy Claudia Hasan; Firmawati; Nur Uyuun I. Biahimo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Stroke survivors generally experience profound emotional changes, such as depression affecting well-being in terms of the patient's quality of life. The purpose of the study was to analyze the relationship between depression rate and quality of life in non-hemorrhagic stroke patients at M.M DUNDA Limboto Hospital. The design of correlational quantitative research with the cross sectional method. The population is all non-hemorrhagic stroke patients at the M.M Dunda Limboto Hospital and samples are taken using purposive sampling techniques and the number of respondents is 32 people. Data analysis was conducted using the Chi square test with a significance level (< 0.05). The results of the study showed that there was a relationship between the level of depression with. Quality of Life in Non-Hemorrhagic Stroke Patients at M.M Dunda Limboto Hospital with p value = (0.000 < 0.05). It can be concluded that the higher the level of depression in non-hemorrhagic stroke patients, the higher the risk of patients experiencing a decrease in quality of life.